FITTING IN: Archaeology and Community in Athienou, Cyprus - Counts, Derek B. ca. 20./21. Jh. (Near Eastern archaeology, 2013)
To what extent do archaeologists distance themselves from the modern people in whose communities they reside while they study the region's past inhabitants? While many projects live and work rather anonymously in communities during field projects, the Athienou Archaeological Project (AAP) has cultivated and benefited from a remarkable, mutually supportive relationship with the town of Athienou, Cyprus. This article highlights four points of community engagement that both govern and structure our relationship with the town: administrative, economic, social, and cultural. Through these points of exchange, AAP has become well integrated with the local community. Through the town's support, we have forged a unique model of archaeology and community that positions the project through our scientific exploration of the region's past as an active agent in illuminating, displaying, and preserving Athienou's rich cultural heritage.